2017
DOI: 10.1182/bloodadvances.2017009670
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic membrane protein LMP1 sequesters TRAF3 in B-cell lymphoma cells to produce functional TRAF3 deficiency

Abstract: Key Points• Expression of the Epstein-Barr virusencoded oncoprotein LMP1 leads to sequestration of TRAF3 in B-lymphoma cells.• This sequestration inhibits TRAF3-negative regulation of prosurvival membrane, cytoplasmic, and nuclear signaling events in the B cell.Loss-of-function mutations in genes encoding the signaling protein tumor necrosis factor receptor-associated factor 3 (TRAF3) are commonly found in human B-cell malignancies, can render B cells functionally TRAF3 deficient without TRAF3 gene mutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The cellular signaling pathways targeted by LMP-1 share functional characteristics with members of the tumor necrosis factor (TNF) receptor superfamily. Molecular studies have revealed that the C-terminal domains (CTAR1 and CTAR2) of LMP-1 play an important role in signal transduction through mimicking the CD40-mediated signaling ( 50 ). The LMP-1 protein binds the tumor necrosis factor receptor-associated factor (TRAF) proteins and the TNF receptor-associated death domain protein (TRADD) activating several intracellular pathways including NF-κB, the mitogen-activated protein kinases JNK and p38, the small GTPase Cdc42, and the JAK/AP-1/STAT cascades.…”
Section: The Lmp-1 Oncogene Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular signaling pathways targeted by LMP-1 share functional characteristics with members of the tumor necrosis factor (TNF) receptor superfamily. Molecular studies have revealed that the C-terminal domains (CTAR1 and CTAR2) of LMP-1 play an important role in signal transduction through mimicking the CD40-mediated signaling ( 50 ). The LMP-1 protein binds the tumor necrosis factor receptor-associated factor (TRAF) proteins and the TNF receptor-associated death domain protein (TRADD) activating several intracellular pathways including NF-κB, the mitogen-activated protein kinases JNK and p38, the small GTPase Cdc42, and the JAK/AP-1/STAT cascades.…”
Section: The Lmp-1 Oncogene Variationmentioning
confidence: 99%
“…The LMP-1 protein binds the tumor necrosis factor receptor-associated factor (TRAF) proteins and the TNF receptor-associated death domain protein (TRADD) activating several intracellular pathways including NF-κB, the mitogen-activated protein kinases JNK and p38, the small GTPase Cdc42, and the JAK/AP-1/STAT cascades. Activation of these intracellular signaling cascades enhances cell survival and proliferation and may account for many of the cellular changes observed in response to LMP-1 ( 50 52 ). Moreover, the LPM1 protein works as homologous to the TNF-receptor family in the B lymphocytes and epithelial cells ( 6 ).…”
Section: The Lmp-1 Oncogene Variationmentioning
confidence: 99%
“…Mechanistically, TRAF3 inhibits the IL-6-IL-6R-JAK1-STAT3 survival and differentiation pathway in plasma cells by facilitating the association of PTPN22 with JAK1 ( 171 ). Furthermore, the EBV-encoded oncoprotein LMP1 sequesters TRAF3 to produce functional TRAF3 deficiency in human and mouse B lymphoma cells ( 172 , 173 ). Intriguingly, lymphocyte-specific TRAF3 transgenic mice also develop plasmacytosis, autoimmunity, inflammation, and cancers, which are likely caused by hyper-responsiveness of B cells to antigens and TLR agonists ( 55 ).…”
Section: Traf3mentioning
confidence: 99%
“…While TRAF3 genetic loss is associated with B cell malignancies, this is not the only mechanism by which a B cell can become TRAF3 protein-deficient, with the tumor-predisposing consequences discussed above. Our laboratory recently reported the results of TRAF3 protein staining of several 100 human DLBCL samples, which revealed that more than 30% of these BCL had low to undetectable TRAF3 protein expression ( 114 ). It was previously demonstrated that the EBV transforming protein LMP1 binds TRAF3 with considerably enhanced affinity, compared to the normal cellular receptor that it mimics, CD40 ( 21 , 23 ).…”
Section: Traf3 and B Cell Malignanciesmentioning
confidence: 99%
“…It was previously demonstrated that the EBV transforming protein LMP1 binds TRAF3 with considerably enhanced affinity, compared to the normal cellular receptor that it mimics, CD40 ( 21 , 23 ). Thus, we examined whether B cell expression of LMP1 is associated with sequestration of TRAF3 in the plasma membrane, resulting in decreased availability of TRAF3 to downregulate various pro-survival signaling pathways discussed above; this was found to be the case ( 114 ). It is also well-documented that signaling to B cells via CD40 or BAFFR leads to poly-ubiquitination and degradation of TRAF3 [reviewed in ( 33 )].…”
Section: Traf3 and B Cell Malignanciesmentioning
confidence: 99%